Analisis Faktor Keberhasilan Pembelajaran Menggunakan Learning Management System (LMS) - Dwi Nila Andriani; Ana Dhaoud Daroin (IKIP PGRI Bojonegoro, 2022)
Abstract: The objectives of this study are 1) To determine the success factors of online learning by utilizing the Learning Management System (LMS) at PGRI Madiun University. 2) Analyze the most dominant factors in the success of online learning using LMS at PGRI Madiun University. The research method used qualitative, with a descriptive approach using a case study at the University of PGRI Madiun. The results show that the factors that influence the success of online learning using LMS are the existence of credit quota assistance for lecturers and students, b) Continuous training from the eLMa team, c) The establishment of the Online Learning and Education Evaluation Technical Implementation Unit (UPT PDEP), d) There is policy from the campus management to use LMS, e) The Covid-19 pandemic which requires Learning From Home (LFH) activities by utilizing the LMS, f) The skills of lecturers in utilizing LMS through various features, so that the material attracts more student interest in learning. The most dominant factor in the success of online learning using LMS is divided into 2 groups, which is seen from the student's point of view and the point of view of the lecturer.Keywords: Learning Management System (LMS), e-learning, eLMA.Abstrak: Tujuan dari penelitian ini adalah 1) Mengetahui faktor-faktor keberhasilan pembelajaran online dengan memanfaatkan Learning Management System (LMS) di Universitas PGRI Madiun. 2) Menganalisis faktor yang paling dominan dalam keberhasilan pembelajaran online menggunakan LMS di universitas PGRI Madiun. Metode penelitian yang digunakan adalah kualitatif, dengan pendekatan deskriptif studi kasus di Universitas PGRI Madiun. Hasil penelitian menunjukkan bahwa faktor-faktor yang menunjang keberhasilan pembelajaran online menggunakan LMS adalah a) adanya bantuan kuota belajar untuk mahasiswa dan dosen, b) pelatihan berkelanjutan dari tim elma, c) pembentukan Unit Pelaksanaan Teknis Evaluasi Pembelajaran dan Pendidikan Online (UPT PDEP), d) adanya kebijakan dari manajemen kampus untu menggunakan LMS e) Pandemi covid-19 yang mengharuskan adanya kegiatan Learning From Home (LFH) dengan memanfaatkan LMS, f) Ketrampilan dosen dalam memanfaatan LMS melalui berbagai fitur, sehingga materi lebih menarik minat belajar siswa. Faktor paling dominan dalam keberhasilan pembelajaran online menggunakan LMS dibagi menjadi 2 kelompok, yaitu dillihat dari sudut pandang mahasiswa dan sudut pandang dosen.Kata Kunci: Learning Management System (LMS; E-Learning; eLMA.